Laparoscopic colorectal surgery for colorectal polyps: experience of ten years - Dulskas, Audrius; Kuliešius, Žygimantas; Samalavičius, Narimantas E. (Acta medica Lituanica, 2017)
Background. Laparoscopy or its combination with endoscopy is the next step for “difficult” polyps. The purpose of the paper was to review the outcomes of the laparoscopic approach to the management of “difficult” colorectal polyps. Materials and methods. From 2006 to 2016, 58 patients who underwent laparoscopic treatment for “difficult” polyps that could not be treated by endoscopy at the National Cancer Institute, Lithuania, were included. The demographic data, the type of surgery, length of post-operative stay, complications, and final pathology were reviewed prospectively. Results. The mean patient was 65.9 ± 8.9 years of age. Laparoscopic mobilization of the colonic segment and colotomy with removal of the polyp was performed in 15 (25.9%) patients, laparoscopic segmental bowel resection in 41 (70.7%) cases: anterior rectal resection with partial total mesorectal excision in 18 (31.0%), sigmoid resection in nine (15.5%), left hemicolectomy in seven (12.1%), right hemicolectomies in two (3.4%), ileocecal resection in two (3.4%), resection of transverse colon in two (3.4%), and sigmoid resection with transanal retrieval of specimen in one (1.7%). Two patients (3.4%) underwent laparoscopicassisted endoscopic polypectomy. The mean post-operative hospital stay was 5.7 ± 2.4 days. There were four complications (6.9%). All patients recovered after conservative treatment. The mean polyp size was 3.5 ± 1.9 cm. Final histopathology revealed hyperplastic polyps (n = 2), tubular adenoma (n = 9), tubulovillous adenoma (n = 31), carcinoma in situ (n = 12), and invasive cancer (n = 4). Conclusions. For the management of endoscopically unresectable polyps, laparoscopic surgery is currently the technique of choice.